Management, competition, acceleration and human rights: either Arsenal, or Plantation, or otherwise? - Jacquinet, Marc (2019)
The present paper aims at discussing the foundation of the current ontology of management, its ethos and the discourse on excellence and efficiency in relation to an abstract and concrete notion of dignity (two versions on dignity). The discussion will focus on several authors such as J. Waldron, C. Beitz, Kant and A. Supiot. Some additional authors are discussed briefly to situate the conception of organizations and work. After a brief discussion some conceptual issues, namely: management, acceleration, plantation economy, human rights and human dignity, the second part of the communication will discuss the foundational elements of management - as disciplinary and scientific discourse, as practice and as an ontology based on money as value. This second section aims at clarifying how the notion of management and some of its origins can be of value to understand current debates on human dignity. The third section discusses the notion of work and organizations and the origins and what is at stake in the current workings of corporations (business corporations) and other types of organizations such as universities. The contrast will be made between Arsenal and the plantation with other forms of organizations.